Pollution Control of HCl Synthesis Unit in Chloro-Alkali Industry. (2016) - Emmanuel, Meijo; Sahadev, Saurabh
Abstract: Control of chlorine gas release is a major concern for most chlor-alkali industries. Normally manual and proportional-derivative-integral control strategies are provided for control. In HCl synthesis plant there are chances of chlorine leakage to atmosphere under certain fault conditions. The limit of chlorine release at stack is 6 ppm and its exposure limit at ground is 2 ppm. If the chlorine release exceeds the limits it may cause pollution problems and in turn will affect human life and environment. This project defines a control strategy to limit the chlorine gas release from the stack by a control mechanism that measures the chlorine concentration at the stack and control the inlet flow rate of chlorine gas to the oven. For this control mechanism PID, Fuzzy logic and Fuzzy-PID strategies are used and of the three, Fuzzy-PID is the best controller which would efficiently limit the release of chlorine gas to atmosphere